A single healthcare experience with Impella RP. Issue 1 (22nd June 2020) - Shekiladze, Nikoloz; Condado, Jose F.; Sandesara, Pratik B.; Kim, Jeong Hwan; Devireddy, Chandan; McDaniel, Michael; Babaliaros, Vasilis; Samady, Habib; Kumar, Gautam; Jaber, Wissam A.
Abstract: Objectives: To understand the predictors of survival and indications for Impella RP in a single healthcare experience. Background: The Impella RP can be used to temporarily support patients with right ventricular (RV) dysfunction after left ventricular assist device (LVAD) placement or myocardial infarction (MI). However, recent postmarket approval data have raised concerns of higher than expected mortality with this device. Methods: A retrospective chart review and analysis of all patients that underwent Impella RP placement in the Emory Healthcare system between January 2016 and December 2018 were performed. Patients were classified according to the indication. Results: A total of 39 patients underwent Impella RP placement. Six patients were post‐LVAD, 9 were implanted for massive pulmonary embolism with persistent shock, 8 for postcardiac surgery RV failure (non‐LVAD), 11 for RV failure post‐MI, and 5 for new or worsening nonischemic cardiomyopathy. The worst survival was noted in MI‐related cardiogenic shock group and in patients who presented with cardiac arrest (3/12). All observed deaths were due to persistent refractory shock. There was no device related death. Survival improved during the last year of experience compared to the first 2 years. Conclusion: This study supports the selective use of the Impella RP, with a higher than national reported survival rate (49% vs. 28.6%). Indication appears to be an important factor determining survival.